Personal listening device usage among Canadians and audiometric outcomes among 6–29 year olds. (1st October 2021) - Feder, Katya; McNamee, James; Marro, Leonora; Portnuff, Cory
Abstract: Objective: To describe personal listening device (PLD) usage and sociodemographic variables among a nationally representative sample of Canadians and examine audiometric outcomes among a subsample. Design: Audiometry and in-person questionnaires were used to evaluate hearing and PLD usage across age, sex, household income/education level. PLD exposure was quantified using a common occupational noise limit. Study sample: A randomised sample of 10, 460 respondents, aged 6–79, with audiometric analysis of a subsample (n = 4807), aged 6–29, tested between 2012 and 2015. Results: Loud PLD usage was reported by19.5% of Canadians. The highest prevalence was among teenagers (44.2%) and young adults (36.3%). Among children, 13.1% of users listened at loud volumes. High PLD usage (equivalent to or above 85 dBA, LEX 40) among 12–19 year olds was double that of 20–29 year olds: 10.2% versus 5.1% E . Five years or more of loud PLD usage was associated with significantly higher mean hearing thresholds compared to less years. No association between loud or high PLD usage and mean thresholds were found. Conclusion: The majority used PLDs safely, however a small proportion reported high risk usage which will impact hearing should this pattern persist over many years.